A cross-diagnostic validation of an instrument measuring participation in everyday occupations: The Occupational Gaps Questionnaire (OGQ). (March 2013) - Eriksson, Gunilla; Tham, Kerstin; Kottorp, Anders
Abstract The aim of this study was to validate the Occupational Gaps Questionnaire (OGQ) when used in samples of people with acquired brain injuries (ABI), stroke, stress-related disorders, concussion, and persons receiving rehabilitation after ABI to investigate whether the OGQ could be used as a generic scale. A total of 601 individuals answered the OGQ at various time points after illness/injury. A Rasch analysis was performed on the data to evaluate evidence of internal scale validity and person response validity, and the capability of the OGQ to separate people into different levels of participation in everyday occupations. The results provided evidence that the OGQ is a valid measure across different diagnostic groups. A generic version of the OGQ can separate at least two levels of perceived occupational gaps and is therefore recommended as a screening tool to be used by occupational therapists working with different diagnostic groups.